La expresión corporal para favorecer el desarrollo de la motricidad gruesa en los niños y niñas del nivel inicial II de la escuela de educación general básica Daniel Rodas Bustamante de la ciudad de Loja, periodo 2018-2019 - Jumbo Fernández, Johana Lilibeth (2020)
This research paper called: BODY EXPRESSION TO FAVOR THE DEVELOPMENT OF THICK MOTORCYCLES IN THE CHILDREN OF THE INITIAL LEVEL II OF THE SCHOOL OF GENERAL EDUCATION DANIEL RODAS BUSTAMANTE OF THE CITY OF LOJA, PERIOD 2018-2019, presented as a general objective: To determine the incidence of body expression in the development of gross motor skills in children of Initial Level II. The research was descriptive, which allowed the description of the problem that exists in the school. The methods used were: scientific, inductive, deductive, and analytical-synthetic. The instruments used for the collection of information were: a survey applied to teachers of initial level II, and the scale of evaluation of psychomotor skills in preschool (De la Cruz and Mazaira). The study sample was 25 people, 23 children and 2 teachers. The results obtained in the pre-test of the Psychomotor Assessment Scale: 57% of the children presented a low level of gross motor skills. After the execution of the proposal, a remarkable improvement in the results was obtained: 78% of the children denote a good level in their gross motor skills. Therefore, it is concluded that the implementation of the proposal based on body expression activities favors the development of gross motor skills.